Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa - Lamboj, Anton; Stiassny, Melanie L.j. (Zootaxa, 2003)
Parananochromis axelrodi, P. brevirostris and P. ornatus, three new cichlid species, are described from Gabon and southern Cameroon. Parananochromis axelrodi is a deep-bodied species differing from congeners in a combination of morphometric and meristic characters. Parananochromis brevirostris and P. ornatus are distinguished by the presence of four elements in the infraorbital series versus five elements in congeners. Parananochromis brevirostris differs from P. ornatus in lacking chest squamation and in the presence of a weakly-developed pharyngeal pad (versus well-developed pad and scaled chest in P. ornatus).